2020
DOI: 10.1101/2020.03.31.018556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatal toxicity of chloroquine or hydroxychloroquine with metformin in mice

Abstract: Guided by the principle of primum non nocere (first do no harm), we report a cautionary note on the potential fatal toxicity of chloroquine (CQ) or hydroxychloroquine (HCQ) in combination with anti-diabetic drug metformin. We observed that the combination of CQ or HCQ and metformin, which were used in our studies as potential anti-cancer drugs, killed 30-40% of mice. While our observations in mice may not translate to toxicity in humans, the reports that CQ or HCQ has anti-COVID-19 activity, the use of CQ resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…In addition, the combination of hydroxychloroquine with metformin is potentially toxic. 25,26 Despite the benefits of hydroxychloroquine on good glycaemic control, long-term use in patients with diabetes is correlated with fatal cardiac arrhythmias and retinal toxicity. Serious ventricular arrhythmias may occur, especially in combination with drugs that prolong QT interval, such as macrolides, antiviral drugs and antihistamines; therefore, a careful risk-benefit assessment should be performed before the use of hydroxychloroquine in patients with diabetes and COVID-19.…”
Section: Treating Patients With Diabetes and Covid-19 Infectionmentioning
confidence: 99%
“…In addition, the combination of hydroxychloroquine with metformin is potentially toxic. 25,26 Despite the benefits of hydroxychloroquine on good glycaemic control, long-term use in patients with diabetes is correlated with fatal cardiac arrhythmias and retinal toxicity. Serious ventricular arrhythmias may occur, especially in combination with drugs that prolong QT interval, such as macrolides, antiviral drugs and antihistamines; therefore, a careful risk-benefit assessment should be performed before the use of hydroxychloroquine in patients with diabetes and COVID-19.…”
Section: Treating Patients With Diabetes and Covid-19 Infectionmentioning
confidence: 99%
“…[6,7] In previous studies indicated that metal nanoparticles of plant extract have strong potentials in treatment of bacterial, fungal, and skin diseases. [8][9][10] Cutaneous wound healing is a dynamic, complex, and regular response to impairment that requires the interaction of different types of cells, structural proteins, growth factors, and proteinases. [11] The basic principles of cutaneous wound healing are minimization of tissue damage, adequate blood supply, oxygenation, proper diet, humid environment to create anatomic integrity, and function of the affected site.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are further concerns about drug interactions (Rajeshkumar et al, 2020). In this way, azithromycin, which was recently used in association with hydroxychloroquine during the COVID-19 pandemic, has been previously shown to slightly increase the risk of cardiovascular death (Ray et al, 2012) and ventricular arrhythmia (Trifirò et al, 2017).…”
Section: Suggestions From the Covid-19 Pandemicmentioning
confidence: 99%